Electron tomography of the nucleoid of Gemmata obscuriglobus reveals complex liquid crystalline cholesteric structure - Yee, Benjamin; Sagulenko, Evgeny; Morgan, Garry; Webb, Richard; Fuerst, John A. (Frontiers in Microbiology, 2012)
The nucleoid of the planctomycete Gemmata obscuriglobus is unique within the Bacteria in being both highly condensed and enclosed by a double-membrane nuclear envelope, seemingly analogous to those of the nucleus of eukaryotes. Here we have applied electron tomography to study high-pressure frozen, cryosubstituted cells of G.obscuriglobus and found multiple nested orders of DNA organization within the condensed nucleoid structure. Detailed examination of the nucleoid revealed a series of nested arcs characteristic of liquid crystalline cholesteric DNA structure. The finest fibres were arranged in parallel concentrically in a double-twist organization. At the highest order of nucleoid organization, several of these structures come together to form the core of the G.obscuriglobus nucleoid. The complex structure of DNA within this nucleoid may have implications for understanding the evolutionary significance of compartmentalized planctomycete cells.